Appeal Against Acquittal By The Prosecutor: Critical Comments on The Indonesian Constitutional Court Decision - Aristo Pangaribuan (Faculty of Law, Jambi University, 2019)
In 2013, the Indonesian Constitutional Court ended the debate concerning the constitutional validity of the right to appeal against acquittal by the prosecutor. Such a question has a long history not only in the Indonesian judicial system. In their decision, the court concluded that the government should have the power to appeal against acquittal to the Supreme Court because of its supervisory function over the lower courts. However, the decision was not unanimous, and there was one dissenting opinion from justice Harjono, who is in favor of protecting the rights of the acquitted defendant. This article is trying to examine the decision and underlined the issue of two competing values, namely ﬁnality, and accuracy that was debated in the decision, even though the court did not explicitly mention it. In the end, this article ﬁnds that the court gives more importance to the accuracy of the conviction and less to their ﬁnality.